DDRT-PCR approaches applied for preeminent results in the isolation of DETs from fish brain tissues - Alves-costa, F. A.; Wasko, A. P. [UNESP] (Instituto Internacional de Ecologia, 2015)
Differential Display (DD) is a technique widely used in studies of differential expression. Most of these analyses, especially those involving fish species, are restricted to species from North America and Europe or to commercial species, as salmonids. Studies related to South American fish species are underexplored. Thus, the present work aimed to describe DD technique modifications in order to improve outcomes related to the isolation of DETs (Differentially Expressed Transcripts), using Leporinus macrocephalus, a large commercially exploited South American species, as a fish design. Different DDRT-PCR approaches were applied to brain samples and the products of the reactions were analyzed on 6% polyacrylamide gels stained with 0.17% Silver Nitrate (AgNO3). The use of PCR reactions under high stringency conditions and longer oligonucleotides based on VNTR (Variable Number of Tandem Repeats) core sequences led to better results when compared to low stringency PCR conditions and the use of decamer oligonucleotides. The improved approach led to the isolation of differentially expressed transcripts on adult males and females of L. macrocephalus. This study indicates that some modifications on the DDRT-PCR method can ensure isolation of DETs from different fish tissues and the development of robust data related to this approach.

Display Diferencial (DD) é uma técnica amplamente utilizada em estudos de expressão diferencial. A maioria desses estudos envolvendo espécies de peixes está restrita a espécies da América do Norte e Europa ou a espécies comerciais, como os salmoniformes. Estudos relacionados a peixes da América do Sul são ainda pouco explorados. Desse modo, o presente trabalho teve como objetivo descrever modificações na técnica de DD, a fim de melhorar os resultados relacionados ao isolamento de DETs (Transcritos Diferencialmente Expressos), utilizando Leporinus macrocephalus, peixe explorado comercialmente na América do Sul, como espécie para tal delineamento. Diferentes abordagens de DDRT-PCR foram desenvolvidas a partir de amostras de tecido cerebral e os produtos das reações foram analisados em gel de poliacrilamida 6% corados com 0,17% de nitrato de Prata (AgNO3). A utilização de reações de PCR sob condições de elevada estringência e oligonucleotídeos mais longos, com base em sequências cerne de VNTR (Número Variável de Repetições em Tandem), mostrou melhores resultados quando comparada a condições de baixa estringência e ao uso de oligonucleotídeos decâmeros. A estratégia empregada permitiu o isolamento de transcritos diferencialmente expressos em machos e fêmeas adultos de L. macrocephalus. Este estudo evidencia que modificações no método de DDRT-PCR garantem o melhor isolamento de DETs a partir de diferentes tecidos de peixes e asseguram a obtenção de dados mais sólidos relacionados a essa abordagem.
Aplicação de abordagens de DDRT-PCR para aprimoramento de resultados no isolamento de DETs a partir de tecido cerebral de peixes
Keywords: Leporinus macrocephalus; Differentially expressed transcripts; VNTR; Leporinus macrocephalus; Transcritos diferencialmente expressos; VNTR